Is Red or Blue More Likely to Narrow the Gap? The Effect of CEO Political Ideology on CEO‐Employee Pay Disparity - Weng, David H.; Yang, Haibin (Journal of Management Studies, 2024)
AbstractHow does CEO political ideology influence the pay disparity between a CEO and typical firm employees? Drawing on the upper echelons theory, we postulate that politically liberal CEOs are more inclined to address within‐firm vertical pay disparity versus conservative or neutral CEOs, because liberals attend more closely to potential inequality issues and are more open to social changes. We furthermore contend that the effect of CEO political ideology varies across certain contextual factors. Results based on a sample of United States public firms support our arguments. Our study contributes to the literature on income inequality by highlighting CEO political ideology as a crucial determinant and investigating the boundary conditions.